2012
DOI: 10.1155/2012/960329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Dengue Virus Circulating in Kolkata, India in 2010

Abstract: Dengue is one of the major public health threats in Kolkata. Every year, blood samples with dengue-like illness are referred to us from different medical colleges and hospitals in Kolkata for the detection of dengue infection in them. In 2010, a total of 378 samples were referred to us for that purpose. All the samples were tested for the detection of IgM antibodies by ELISA method, followed by RT-PCR test for the detection of serotypes. Only 173 samples were ELISA positive. Out of 378 samples, 108 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
7
18
4
Order By: Relevance
“…It has risen to epidemic proportions and is endemic to many areas, both urban and rural. In our study highest prevalence was seen in the age groups between 11-50 years and with male preponderance which is seen in other studies also (Gupta et al, 2006;Chakravarti et al, 2005;Sarkar et al, 2012). The sensitivity of the rapid ICT tests for NS1 Ag& IgM in our study was more than 90%, and specificity more than 98% when compared to ELISA.…”
Section: Resultssupporting
confidence: 70%
“…It has risen to epidemic proportions and is endemic to many areas, both urban and rural. In our study highest prevalence was seen in the age groups between 11-50 years and with male preponderance which is seen in other studies also (Gupta et al, 2006;Chakravarti et al, 2005;Sarkar et al, 2012). The sensitivity of the rapid ICT tests for NS1 Ag& IgM in our study was more than 90%, and specificity more than 98% when compared to ELISA.…”
Section: Resultssupporting
confidence: 70%
“…11,12 Sarkar A et al, however, reported maximum cases in the age group 0-10 years with female preponderance (Figure 1, 2). 13 All of the cases were reported during the Rainy seasons, in accordance with the reported patterns of dengue transmission in monsoon and post monsoon season. 14,8 Environmental conditions favoured an explanation of Aedes aegypti and dengue virus transmission.…”
Section: Discussionsupporting
confidence: 83%
“…Findings of Gupta et al 12 andChakravarti and Kumaria 13 were similar to our studyi.e., maximum cases was in the age group (21-30 years) and in the finding that the male patients clearly outnumberingthe female patients. However Sarkaret al 14 reported that maximum cases were in the age group ≤10 years and there was female preponderance in their study. The majority of the cases were reported during the post-monsoon seasons (August to November) with a peak during October and November in all the four years (2012)(2013)(2014)(2015), in accordance with the established findings by P. Reiter.…”
Section: Discussionmentioning
confidence: 71%